Model and control on the ascending process of rotating wing helicopter - Noor Zalika, Kornain (2013)
The aim of this research project is to develop an autopilot system that enables the helicopter model to carry out autonomous hover manoeuvre using on-board intelligence computer. The main goal of this project is to provide a comprehensive design methodology, implementation and testing of an autopilot system developed for a rotorcraft-based unmanned aerial vehicles (UAV). The autopilot system was designed to demonstrate autonomous manoeuvres such as take-off and hovering flight capabilities. For the controller design, the nonlinear dynamic model of the helicopter was built comprising of four different subsystems such as actuators dynamics, rotary wings dynamics, force and moment generation process and rigid body dynamics. Stabilization of the helicopter was derived by using Proportional Integral Derivative method. The overall system consists of the helicopter with an on-board computer and a second computer serving as a ground station. While flight control is done on-board, mission planning and human user interaction take place on ground. Sensors used for autonomous operation include acceleration and euler angles sensors The hardware and software used to autonomously pilot the helicopter were described in detailed in this thesis. Series of test flight were conducted to verify autopilot system performance. The proposed hovering controller has shown capable of stabilizing the helicopter attitude angles.